Community Structure of South Sudan state and its impact on national integration (Journal of the College of Education for Women, 2019)
South Sudan is known by its tribal and racial variation .Tribal Perception represents theprocedure of dealings in Southern society .And that what make Sudan as a stable country thatsuffer from divisions . Everybody wants to rule in spite of his inability and un qualificationwhich enables the establishment of an urbanized country .the frustration of the state inhandling the interior variety on religious, tribal and racial basis and contracting nationalideality in spared by shared ingredients between gathered groups in one state, all these reasonsmake it hard to create a united national identity which is able to unite atheist and religiousparties together. Due to this ,the study is established to clarify the national fusion in the southof Sudan and it tackles the crises and the problems that prevent the success of the nationalfusion . One of the problems is the problem of (Aby, the south of blue Nile and kardafan).thestudy suggested some special solutions about the national fusion like the activity of theadministration in setting down and fixing the tribal and dissociating conflicts. Such solutionswill be done by giving the opposing members equal active participation in authority whichwill facilitate enriching the national fusion. Suitable space will be given for making suitabledecision which will not affect sovereign authority but add a sense of belonging .Father more,it settles the indulgence , comprehending and to levance for the existed variety in the state . Ithelps in the dispensation of the problems that forms an obstacle in the national fusion.